2011
DOI: 10.2147/ijwh.s22853
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of stereotactic core breast biopsy and open surgical biopsy results at a tertiary care hospital in Pakistan

Abstract: BackgroundThe purpose of this study was to determine the yield of stereotactic core breast biopsy and its cost-saving potential.MethodsThis observational study was conducted at the Department of Radiology at Aga Khan Hospital in Karachi. All female patients (n = 84) undergoing stereotactic core breast biopsy under mammographic guidance from January 2005 to May 2010 were included. Stereotactic core biopsy was performed on a dedicated mammography unit employing a 14-gauge needle with an automated biopsy device. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Fibroadenoma is a common benign tumor, resulting from an excess proliferation of connective tissue and is often subjected to percutaneous biopsy [28]. A study by Masroor et al showed that 80% of all biopsied breast lesions were benign in the Pakistani population [29]. This is similar to other studies, that have reported a cancer detection rate of only 10%-30% on breast biopsy [17].…”
Section: Discussionmentioning
confidence: 56%
“…Fibroadenoma is a common benign tumor, resulting from an excess proliferation of connective tissue and is often subjected to percutaneous biopsy [28]. A study by Masroor et al showed that 80% of all biopsied breast lesions were benign in the Pakistani population [29]. This is similar to other studies, that have reported a cancer detection rate of only 10%-30% on breast biopsy [17].…”
Section: Discussionmentioning
confidence: 56%
“…Furthermore, the biopsy results strongly influence the algorithm for evaluation of suspicious lesions. 16 …”
Section: Discussionmentioning
confidence: 99%
“…Most of all, surgery can place a large burden on patients. The morbidity, mortality and the cost in surgery have been discussed as disadvantage of surgery in previous study and wire localization is necessary for non-palpable lesions (3,21). If the wire inadvertently dislodges, migrates or is transected, the surgeon can become disoriented and excise the wrong tissue (22).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, ST-VAB is a safe and effective method for nonpalpable mammographically visible microcalcifications or masses, and can yield large amounts of tissue (1)(2)(3)(4)(5). Furthermore, a lower re-biopsy rate and a fewer cases of histologic underestimation of ST-VAB with this method compared to core needle biopsy (CNB) were reported (5).…”
Section: Introductionmentioning
confidence: 99%